Emerging Role of Nanotechnology in Engineering Education - Praveen, Kulkarni; Prayag, Gokhale; YM, Satish; Basavaraj, Tigadi (Journal of Engineering Education Transformations, 2022)
The present research comprehends role of nanotechnology in providing career opportunities for engineering graduates. This study was essential as Nanotechnology has multiple applications in the field of engineering science. Therefore, perception of the engineering students was captured in the study. Structural equation modeling is adopted in the study to understand the perception of the respondents. The research findings indicate that nanotechnology provides a direction for engineering graduates in enhancing the career opportunities. The findings of this study are also useful and supports policymakers and education institutes in the domain of engineering education.